2001
DOI: 10.1016/s0006-3495(01)75915-2
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Monohydrate Nucleation in Ultrathin Films on Water

Abstract: The growth of a cholesterol crystalline phase, three molecular layers thick at the air-water interface, was monitored by grazing incidence x-ray diffraction and x-ray reflectivity. Upon compression, a cholesterol film transforms from a monolayer of trigonal symmetry and low crystallinity to a trilayer, composed of a highly crystalline bilayer in a rectangular lattice and a disordered top cholesterol layer. This system undergoes a phase transition into a crystalline trilayer incorporating ordered water between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
124
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(148 citation statements)
references
References 23 publications
22
124
0
2
Order By: Relevance
“…The registration of the bilayers can be altered by a different pattern of water molecules between the layers. An illustrative analogy is the crystal structure of the cholesterol derivative stigmasterol, which has been reported recently (29). The overall packing of stigmasterol molecules is similar to that of cholesterol, but with less than one water molecule per sterol, thus forming a stigmasterol hemihydrate.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The registration of the bilayers can be altered by a different pattern of water molecules between the layers. An illustrative analogy is the crystal structure of the cholesterol derivative stigmasterol, which has been reported recently (29). The overall packing of stigmasterol molecules is similar to that of cholesterol, but with less than one water molecule per sterol, thus forming a stigmasterol hemihydrate.…”
Section: Discussionmentioning
confidence: 91%
“…Recent studies of cholesterol crystal nucleation upon an air-water interface (29,30), as well as diffraction electron microscopy studies of cholesterol films in bile (24), cast additional light on the pathway by which helical ribbons may be formed. Both studies show that thin cholesterol crystals have rectangular unit cell, with a ϭ 10 and b ϭ 7.5 Å.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that cholesterol enriched macrophage cells form cholesterol crystals near the cytoplasm membrane, 44 and it was suggested that these crystals nucleate at the lipid membrane. 20, 40, 45 We hereby demonstrate that the nucleation of cholesterol crystals can occur within DPPC:Chol:POPC bilayers and discuss the conditions for nucleation.…”
Section: Introductionmentioning
confidence: 80%
“…Similarly, the abundant HHP product from CholSO 4 ozonolysis is attributed to a relatively low water density in the CholSO 4 interfacial layer. At the air-water interface, Chol assembles in ordered crystalline structures up to three molecular layers thick [34,35]. Analysis using X-ray diffraction indicates that the Chol crystalline phase on the liquid surface comprises Chol monohydrate crystallites [35].…”
Section: Air-liquid Interfacial Reaction Of Cholso 4 With Omentioning
confidence: 99%
“…At the air-water interface, Chol assembles in ordered crystalline structures up to three molecular layers thick [34,35]. Analysis using X-ray diffraction indicates that the Chol crystalline phase on the liquid surface comprises Chol monohydrate crystallites [35]. It is expected that CholSO 4 interacts with water molecules to a greater extent than Chol due to its anionic sulfate head group.…”
Section: Air-liquid Interfacial Reaction Of Cholso 4 With Omentioning
confidence: 99%